INTENSIFICATION OF HEAT TRANSFER IN A HIGH-TEMPERATURED FLUIDIZED BED - Redko, A. O.; Redko, I. O. (Science and Transport Progress, 2017)
Purpose. This paper highlights experimental research of heat exchange in coarse particles to ensure the performance of ecological characteristics of Heat supply system. Methodology. The test stand has been developed to solve the defined task. It helps to do the research at the temperature of fluidizing bed and pulsating fluidizing bed at the range 800–1000°С. The temperature of the fluidized bed was provided by burning natural gas and wood waste. Sand and chamotte with a particle size of 1.0 to 5.0 mm were used as the layer material. The heat-transfer coefficient from the layer to the surface, immersed in the layer, and the density of the heat flux were measured by a calorimetric method under steady-state conditions. Smooth tubes and transversely finned with different height and rib spacing were investigated. Experiments in a high-temperature pulsating fluidized bed were carried out with pulsating combustion of natural gas in a layer or in a sublattice chamber into which natural gas and air were separately supplied. The frequency of combustion pulsations was provided by the automation system. The flash frequency was regulated in the range from 0.14 to 5 Hz. Findings. It is presented the results of physical modeling to find out the heat-transfer coefficients of smooth and finned tubes in fluidizing bed of coarse particles in the process of wood waste and gaseous fuel combusting. It is proved that the coefficient of heat transfer increases with increasing temperature by 2–2,5 times in the bed which contains particles diameter of 2.5–5 mm is 300–350Vt/(m2 К) that is much higher than for layer furnaces. The results of the experiments are presented in the form of a generalized relationship that takes into account the diameter of the particles and the value of the finning coefficient. Heat transfer of finned tubes is 15–20% less then smooth tubes but the density of heat flow referred to the area of a finned tube is 0,12–0,20 МVt/m2 that is higher than for smooth ones. At pulsating fuel supply with frequency 1-2 Hz the heat-transfer coefficient gets higher from 10–15% till 25–30%. At a ripple frequency of 2 to 5 Hz, the heat-transfer coefficient varies from 510 to 570W/(m2K). With a further increase in the pulsation frequency, the heat-transfer coefficient decreases and amounts to 515–520 W/(m2K). A significant effect of the ripple pulsation from 0.8 to 0.3 is shown: the heat-transfer coefficient is increased by 30–35%. However, an unstable combustion regime of the gas-air mixture and the ejection of material particles from the layer are observed. The results of the experiments are presented in the form of a generalized relationship. Originality. The authors have presented the obtained experimental data about heat-transfer coefficients of finned tubes in fluidizing bed and pulsing fluidizing bed of coarse particles at the temperature of layer 800–1100оС. Practical value. The results obtained at the research help to develop furnace devices with low-temperature fluidizing bed in the process of immersion in a layer of finned tubes layers. The research data is presented in criterial view which is convenient for practical using.